Genome-wide analysis of the AarPDR gene family in Artemisia argyi and its potential role in regulating terpenoids transport - Xiaoyu Han; Min Cui; Shuangxin Ma; Xuemei Gao; Liping Tang; Bin Li (BMC Plant Biology)
Abstract Background The pleiotropic drug resistance (PDR) proteins, which are full-sized ABCG transporters belonging to the ATP-binding cassette (ABC) family, play an indispensable role in regulating various physiological and developmental processes of plants. However, the PDR transporters and their functional roles in Artemisia argyi, a significant traditional medicinal plant in Asia, remain poorly understood. Results In this study, a total of 68 PDR genes, distributed across 17 chromosomes, were identified in the genome of Artemisia argyi and classified into five distinct subgroups based on phylogenetic analysis and domain types. The evolutionary characteristics investigation of the AarPDR gene family demonstrated that the 9 AarPDR genes had a high conservation between the genomes of Artemisia argyi and Arabidopsis during the evolution of dicots. Cis-element analysis revealed that AarPDRs might respond to diverse environmental stresses and multiple plant hormones. Furthermore, the expression analysis in different tissues and developmental stages of leaves indicated that various AarPDRs displayed distinct expression profiles within or among subfamilies, and the AarPDRs expression could be easily induced by the light conditions. Besides, the AarPDR family proteins had a potential function in metabolite transportation. Conclusions The AarPDRs were characterized by integrating genome analysis, transcriptome, and metabolite profiling. The results can provide useful clues for future studies aimed at the functional characterization of AarPDR genes.